PREDICTORS OF LENGTH OF CARE IN TIBIAL FRACTURE PATIENTS: ANALYSIS OF SECONDARY DATA: PREDIKTOR LAMA PERAWATAN PADA PASIEN FRAKTUR TIBIA: ANALISIS DATA SEKUNDER - Hakam, Mulia; Pratama, Fernanda Reza; Ridla, Akhmad Zainur (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2022)
Introduction: Predicting the length of care becomes important for intervention in the care system. However, it still seems that the ability to predict the length of treatment is not optimal, so that the length of treatment is prolonged. If the ability to predict the length of treatment can be done optimally, it will improve the patient's return time. Methods: This study uses a retrospective study approach. Result: There was no relationship between the predictor of length of stay with a length of treatment. Conclusion: The predictor of length of stay in this study were patients with tibia fractures at RSD dr. Soebandi. Most of the patients with tibial fractures were in the early elderly, with the gender of patients with tibia fractures being mostly male. Most of the patients with tibial fractures have no complications and the type of fracture in patients with tibia fractures is mostly in the fracture of the shaft of the tibia. There was no correlation between the predictors of length of stay and length of stay in patients with tibia fractures.